ISOLATION AND DIAGNOSIS OF E. COLI BACTERIA FROM THE URINARY TRACTS OF PREGNANT WOMEN AND THE EFFECT OF SOME ANTIBIOTICS AND EXTRACTS ON THEM - Haneen Deyaa Majed (Web of Journals Publishing, 2024)
Randomly studied (100) cases of urinary tract infection of pregnant women in the first three months of pregnancy were studied at Salah al-Din General Hospital in the city of Tikrit during the year 2023. (68) bacterial infections were obtained, including E.coli bacteria, and these bacteria were isolated in a percentage of (44) isolates. Studies showed that women in the city had a lower rate of urinary tract infections than pregnant women in rural areas. The study also showed that educated pregnant women are less likely to suffer from urinary tract infections than uneducated pregnant women. The study results showed the trend of the antibiotics used towards Gram-negative bacteria, as the antibiotic Imipenem gave the highest percentage of inhibition, while Nitrofurantoin gave the average percentage, and Erythromycin had the most minor effect on the isolated bacteria. Ginger extract was also used on the bacterial species isolated from the urinary tract and the extent of the effect of the aqueous and alcoholic extract of ginger on it was demonstrated as the alcoholic extract had a higher inhibition on the isolated bacteria.
Keywords: Isolation, Diagnosis, E. coli bacteria, Urinary tracts, Pregnant women.